Narratives of the collective “la comadre” on the strategy of income generation in the District of Cartagena (Revista de Investigaciones Universidad del Quindío, 2021)
The article presents some results and reflections of the research “Perceptions of the Collective “La Comadre” around the strategy of generating income of the public policy of displacement victims in the city of Cartagena”, whose main objective was to analyze the perceptions built by Afro-Colombian women of the collective La Comadre around the revenue generation strategy of the Public Policy of Victims of Forced Displacement implemented in the District of Cartagena de Indias, to identify current challenges on the articulation between public policies, social organizations and governance in the territory.In this way, the research process was worked from a qualitative approach and a hermeneutic and phenomenological paradigm that allowed to carry out an approach and analysis to the perceptions built by the Collective and, in turn, was identified from the narratives of women and the voices of public and academic officials bets on the strengthening of public policies in relation to the generation of income for Afro-Colombian women.In this regard, knowing the perspectives of women, civil servants and academics showed nonconformity in relation to income-generating actions for displaced Afro-Colombian women; likewise, from its narratives, it is stated that there are major challenges for the District of Cartagena related to significant advances in terms of implementation and compliance with public policies oriented to revenue generation.
Keywords: Perceptions; forced displacement; victims of armed conflict; public policies; income generation